Bacillus Calmette-Guerin lymphadenitis in children: an underdiagnosed entity - Singh, Neha; Gupta, Prajwala (International Journal Of Community Medicine And Public Health, 2024)
Background: Bacillus Calmette-Guerin (BCG) lymphadenitis is a common complication after BCG vaccination. Fine needle aspiration cytology (FNAC) is a feasible and cost-effective procedure for the diagnosis and management of this entity. Awareness of this entity in cytology is important to avoid misdiagnosis, as the cytomorphologic features are very similar to tuberculosis. The present study described the clinical presentation and detailed cytomorphologic features in patients with BCG lymphadenitis. Methods: This was a retrospective study from 2018 to 2022 involving a total of 27 patients who presented with isolated left axillary or cervical lymphadenopathy. Results: Age at presentation ranged from 1 to 24 months. The male- to-female ratio was 2.75:1. Majority of the children had enlargement of the left axillary lymph nodes followed by cervical nodes. Cytomorphology showed the presence of dense acute and chronic inflammatory cells, epithelioid cell granulomas, multinucleated giant cells, histiocytic aggregates, reactive lymphoid cells, lymphohistiocytic clusters and calcification. Necrotic background was present in 25 (92.6%) cases. Ziehl-Neelsen staining for acid-fast bacilli was positive in 17 (62.9%) cases. Conclusions: A high index of clinical suspicion for BCG lymphadenitis should be kept in mind for children who are recently vaccinated. Diagnosis of this entity is based primarily on clinical grounds. However, cytology and microbiological examination are encountered as part of clinical work up of lymph node swelling. FNAC in conjunction with clinical presentation is useful for diagnosis of BCG lymphadenitis and avoid an unwarranted tubercular treatment.